Juridical Analysis of the Concept of State Responsibility towards Natural Disaster Victims Based on Indonesian Law Number 24 of 2007 on Disaster Management - Nur Iqbal N, Muh.; Awaluddin, Ahmad Reski; Liweng, Andi Darmawansya Tenri (Manunggal Halim Jaya, 2024)
This research aims to analyze the concept of state responsibility towards natural disaster victims. Case study on the impact of the earthquake in West Sulawesi in 2021. The approach used is a philosophical approach. The research method used is a mixed qualitative and quantitative approach. The primary data used consists of interview data conducted with the Head of the BPBD of West Sulawesi Province, the Head of the Social Service of West Sulawesi Province, the Head of Law and Human Rights of West Sulawesi, and the community victims of Natural Disasters in West Sulawesi Province. The secondary data used includes (1) Primary legal materials, which are all related regulations such as the 1945 Constitution and Law No. 39 of 1999 on Human Rights. (2) Secondary legal materials, which provide explanations of primary legal materials in the form of laws written in journals by legal scholars, and theories or opinions of experts such as the theories used, namely the theory of state responsibility, the theory of legal protection, and the theory of human rights. (3) Tertiary legal materials, which provide guidance in the form of dictionaries, encyclopedias, and books that explain primary and secondary legal materials. The research results show that the sustainability of victim handling and the effectiveness of social assistance guarantee implementation are influential factors on the state's responsibility towards natural disaster victims. The importance of human rights-based policies, coordination between the central, provincial, and regional governments, and the fulfillment of basic needs to ensure the state's responsibility towards victims are met.